Report on Environmental Management System (EMS) Workshop, 1st Regional Conference on Campus Sustainability (1RCCS) 2014 - Mohd Din, Shamzani Affendy (UMS Press, 2014)
All aware that in order to implement EMS in any institutions, it will involve all participations and understanding by the top management, executive and technical and non-technical groups. This reflect to the amount of budget need to be provided by the institutions in getting the ISO 14001 and implementing ems as a whole and also to sustain the professional certification in the future. Besides, without financial support the initiatives will be lot difficult and may not be materialized. However, there are always options in getting the certification application on a small scale for example focusing in one particular scope like solid waste management, air pollution, energy conservation, etc. or it can be as the whole package as one.